2018
DOI: 10.3390/cancers11010028
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids in Cancer and Apoptosis

Abstract: Cancer is the second leading cause of death globally. Although, there are many different approaches to cancer treatment, they are often painful due to adverse side effects and are sometimes ineffective due to increasing resistance to classical anti-cancer drugs or radiation therapy. Targeting delayed/inhibited apoptosis is a major approach in cancer treatment and a highly active area of research. Plant derived natural compounds are of major interest due to their high bioavailability, safety, minimal side effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
427
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 534 publications
(434 citation statements)
references
References 274 publications
5
427
0
2
Order By: Relevance
“…Naringenin anticancer effect arrests cell development at the G0/G1 phase; inhibits Candida spp. growth [39,43,60] 18 Naringin anticancer effect arrests cell development at the G0/G1 phase; inhibits Candida spp. growth [39,43,60] 20 Luteolin anticancer associated with the induction of apoptosis, and inhibition of cell proliferation, metastasis and angiogenesis [60,86]…”
Section: Electrochemical Evaluation Of Antioxidant Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…Naringenin anticancer effect arrests cell development at the G0/G1 phase; inhibits Candida spp. growth [39,43,60] 18 Naringin anticancer effect arrests cell development at the G0/G1 phase; inhibits Candida spp. growth [39,43,60] 20 Luteolin anticancer associated with the induction of apoptosis, and inhibition of cell proliferation, metastasis and angiogenesis [60,86]…”
Section: Electrochemical Evaluation Of Antioxidant Capacitymentioning
confidence: 99%
“…Epicatechin anticancer activity [60,88] 25 Apigenin anticancer effect by arresting cell development at the G0/G1 phase; the inhibition of phosphorylation of mitogen-activated protein kinase (MAPK) [60] 26 Orientin antioxidant, antiviral and antibacterial activities, anti-inflammatory neuroprotective or antidepressant-like effects [89] 3. Materials and Methods…”
mentioning
confidence: 99%
“…Research on natural compounds as potential source of anti-cancer drugs is generating considerable interest to invest more in plant-based research. Mechanistic studies evaluating therapeutic potential of plant based compounds reveal multi targeted action on the target cell [164]. The principle behind any therapeutic approach against tumor growth is essentially by targeting the hallmarks of cancer, miRNA profiling of different cancers reveals a striking association of miRNA with all stages (cancer hallmarks) of the cancer progression.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…Jazzara et al [170] concluded that λ-carrageenan (sulfated galactans found in certain red seaweeds) could be a promising bioactive polymer, showed a remarkable inhibitory effect on MDA-MB-231(triple negative breast cancer cell line) cell migration [171]. Several studies support polyphenols [172][173][174][175][176], flavonoids [177][178][179][180][181][182][183][184][185][186], fucoidan [159,160,166,[187][188][189][190][191][192][193][194][195], lutein/zeaxanthin [196][197][198][199][200], other seaweed alkaloids, peptides, tannins and polysaccharides [132,164,[201][202][203][204][205][206][207][208][209][210] in breast cancer management. The number of deaths from colorectal cancer in Japan continues to increase [211], it is the third most common diagnosis and second deadliest malignancy for both sexes combined…”
Section: Cancer Prevention and Tumor Controlmentioning
confidence: 99%